Sistem Finansial Pendidikan di Indonesia (Analisis Tentang Signifikansinya Terhadap Pengelolaan Human Capital) - Aminuddin Aminuddin; Ahmad Sukri Harahap; M. Nuh Dawi (Hikmah, 2021)
This study aims to analyze the financial system of education in Indonesia, which focuses on the management of Human Capital. The research method used in this study is Library Research, with documentation data collection techniques, while data analysis uses content analysis techniques. The results of the study explain that education is very influential on the economy of a nation. Education can not only make people who are knowledgeable, educated, and know technology, but education can be used as a means to support economic growth. Because with education, humans make new innovations that support the economy in accordance with the times. Education as human capital or human investment is because education is the most important investment in human capital to answer today's global challenges. Education is a vital component in the growth and development of a country. The dual role of education, namely as input and output, makes education very important in economic development. Education in developing countries plays a role in shaping the country's ability to absorb modern technology and develop capacity to create sustainable growth and development.